2022
DOI: 10.3389/fgene.2022.1077729
|View full text |Cite
|
Sign up to set email alerts
|

Mutation spectrum of PTS gene in patients with tetrahydrobiopterin deficiency from jiangxi province

Abstract: Background: Hyperphenylalaninemia (HPA) is the most common inborn error in amino acid metabolism. It can be primarily classified into phenylalanine hydroxylase (PAH) deficiency and tetrahydrobiopterin (BH4) deficiency. BH4 deficiency (BH4D) is caused by genetic defects in enzymes involved in the biosynthesis and regeneration of BH4. 6-pyruvoyl-tetrahydropterin synthase (PTPS/PTS), which is encoded by the PTS gene, participates in the biosynthesis of BH4. PTPS deficiency (PTPSD) is the major cause of BH4D. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…In the present study, BH4D accounted for 15.87% of patients with HPA, which is similar to the proportion reported for Taiwan ( Niu et al, 2010 ). In addition, 29 out of the 30 (96.67%) patients with BH4D in our study had PTPSD, which is consistent with previous studies ( Ye et al, 2013 ; Han et al, 2015 ; Xie et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, BH4D accounted for 15.87% of patients with HPA, which is similar to the proportion reported for Taiwan ( Niu et al, 2010 ). In addition, 29 out of the 30 (96.67%) patients with BH4D in our study had PTPSD, which is consistent with previous studies ( Ye et al, 2013 ; Han et al, 2015 ; Xie et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…Only a few studies to date have investigated the prevalence of BH4D, with a global incidence of approximately 1 in 500,000 live births ( Blau et al, 2018 ); however, wide variation in the estimated prevalence has been reported depending on the geographical location and ethnic composition of the different provinces in China ( Wang et al, 2021 ; Xie et al, 2022 ). The prevalence of BH4D in the northern regions (4.1 per 1,000,000) of China is reportedly higher than that in the southern regions (1.6 per 1,000,000) ( Yuan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The c.84-3C > G variant is considered pathogenic in the ClinVar database (Variation ID: 553378), and was previously reported to be associated with as a severe form of PTPSD in Albania, Italy, and Iran [ 9 , 18 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%